The Medicina Plinii - Hunt, Yvette, author.
1 online resource.
Keywords: This book presents the first ever English translation of the Medicina Plinii, one of the most influential books of applied medicine and self-medication in Late Antiquity and the Middle Ages. The work, which predates AD 400, was created as a quick reference work for travellers, and became and remained highly influential, as witnessed by frequent references to it and by various later adaptations. Only the rise of scientific medicine and pharmacology led to its demise and confinement in a small corner of specialist studies. It presents more than 1,150 healing methods and recipes mainly adapted from the encyclopedic Natural History of Pliny the Elder, arranged from the patient's head to foot in order that readers could quickly find treatments for their diseases. The Medicina Plinii is of dual interest to present-day scholarship: The book is a monument for the practical application of classical knowledge which has recently found lively interest in the history of science and medicine. At the same time the Medicina Plinii provides a fascinating insight into the realities of the world of Late Antiquity, and into the anxieties of the people living in the vast Roman empire. This book will be of particular interest to scholars and advanced students in the History of Science and Medicine, along with a wider audience interested in medicine, and in life in the Roman world.